KUALITAS PRODUK DAN DAMPAKNYA TERHADAP KEPUTUSAN PEMBELIAN GITAR ARISTONE PADA CV. ARISTA BANDUNG - Restiani Widjaja, Yani; Nurdiyana, Gani (Coopetition : Jurnal Ilmiah Manajemen, 2018)
This study aims to determine the magnitude of the effect of product quality on purchasing decisions and to test whether there is a significant influence between product quality and purchasing decisions on Aristone guitar products in Bandung. The research method used is the research method of verification analysis, by conducting validity test, reliability test, simple regression analysis, simple coefficient analysis, and determination analysis. Based on statistical tests conducted, t test showed that there is a significant effect of product quality variables on consumer purchasing decisions on Aristone guitar products in Bandung. From the results of the correlation coefficient analysis is obtained that if the product quality increases, it will be followed by an increase in consumer purchasing decisions, and vice versa. The degree of relationship between product quality and consumer purchase decisions is strongly interpreted. The coefficient of determination shows the contribution of product quality (X) to consumer purchase decision (Y).